2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Transportation -- Motor Carrier Safety Regulations for Transporting Migrant Farm Workers [Federal] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS, 2003)
Motor Carrier Safety Regulations establishe safety and other standards regarding the transportation of migrant farmworkers. This is EDIS document FE418, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.